CYTOGENETICS EFFECT OF SODIUM SULPHATE ON REPRODUCTIVE IN MUS MUSCULUS - الركابي, عبد الامير; جبير, اشواق; لفتة, فاضل (Iraqi Journal of Science, 2024)
The aim of this study was to detect the cytogenetic effect of sodium sulphate through using cytogenetic analysis ( mitotic index and chromosomal aberrations on somatia and germ cells ) and sperm head abnormalities on white mice .Ninety eight male mice were used in this study . To test the effect on each indicator , these animals were divided into two groups . The first one was the control group while the second was treated with sodium sulphate . The result refer that the sodium sulphate cause an inhibition of the mitotic index in somatic and sex cells and the inhibition increased by augmenting the concentration . Such difference were significant (P<0.01) . The influence of the doses was significant in the case of the somatic cells (P<0.05).The chromosomal aberrations increased pursuant to the raising of sodium sulphate concentration , the influence was significant (P<0.01) . The doses had an effect on the occurrence of aberration (P<0.05) in case of chromatid breaks of the sex cells only , sodium sulphate brought about a significant augmentation (P<0.01) in sperm head abnormality , with their different kind period were without significant effect